Hubungan Antara Motivasi Belajar dengan Hasil Belajar IPS di Kelas IV SDN 4 Bawu - Widodo, Rahmad Singgih; Anintyawati, Riska (Indo-MathEdu Intellectuals Journal, 2025)
This research aims to determine whether or not there is a relationship between learning motivation and the learning outcomes of social studies for fourth-grade students at SDN 4 Bawu. A correlational quantitative research design was used to analyze the relationship between the two variables. Data were collected from 36 students using a structured motivation questionnaire and documented social studies test scores. The data collection technique used in this study was a questionnaire. The research instrument was compiled based on learning motivation indicators. The instrument validation test used Pearson's Product Moment correlation formula, while the reliability test used Cronbach's Alpha formula. Data analysis techniques included descriptive analysis, prerequisite analysis tests such as normality and linearity tests, and hypothesis testing using correlation tests with the Product Moment correlation formula. The research results show that there is a very strong and significant relationship between learning motivation and social studies learning outcomes at SDN 4 Bawu, with a correlation coefficient of 0.687, and an r-table at a significance level of 5% of 0.329. Thus, there is a significant relationship between learning motivation and student learning outcomes. This indicates that learning motivation is an important factor in achieving student learning outcomes. The research results indicate that there is a significant relationship between learning motivation and learning outcomes of fourth-grade students at SDN 4 Bawu.